Innovative and Constructivist Digital-Based Learning Model in Increasing Adults’ Learning Interest - Nur Ida; Ihwan Ridwan (Universitas Negeri Semarang, 2023)
This study used a quantitative approach in which the design was experimental and the control group with pre-test and post-test. Data analysis of learning residents involved 25 people. Interviews, observations, questionnaires, and documentation were all used to gather data. The findings of this study suggested that innovative learning models were developed using empirical and theoretical studies, and they contributed significantly to evidence of their viability based on the findings of analyses of different stakeholders so that the model could be applied. The results of the application of the innovative learning model with the model test phase I to phase II showed an increase in interest in learning. In conclusion, the application of innovative learning models for learning citizens has been effectively digital-based. This was indicated by the increasing interest in adult learning.